Extracellular matrix substrates differentially influence enteric glial cell homeostasis and immune reactivity - Schneider, Linda; Schneider, Reiner; Hamza, Ebrahim; Wehner, Sven (Frontiers in Immunology, 2024)
Introduction: Enteric glial cells are important players in the control of motility, intestinal barrier integrity and inflammation. During inflammation, they switch into a reactive phenotype enabling them to release inflammatory mediators, thereby shaping the inflammatory environment. While a plethora of well-established in vivo models exist, cell culture models necessary to decipher the mechanistic pathways of enteric glial reactivity are less well standardized. In particular, the composition of extracellular matrices (ECM) can massively affect the experimental outcome.Considering the growing number of studies involving primary enteric glial cells, a better understanding of their homeostatic and inflammatory in vitro culture conditions is needed.We examined the impact of different ECMs on enteric glial culture purity, network morphology and immune responsiveness. Therefore, we used immunofluorescence and brightfield microscopy, as well as 3' bulk mRNA sequencing. Additionally, we compared cultured cells with in vivo enteric glial transcriptomes isolated from Sox10 iCreERT2 Rpl22 HA/+ mice.We identified Matrigel and laminin as superior over other coatings, including poly-Lornithine, different lysines, collagens, and fibronectin, gaining the highest enteric glial purity and most extended glial networks expressing connexin-43 hemichannels allowing intercellular communication. Transcriptional analysis revealed strong similarities between enteric glia on Matrigel and laminin with enrichment of gene sets supporting neuronal differentiation, while cells on poly-L-ornithine showed enrichment related to cell proliferation. Comparing cultured and in vivo enteric glial transcriptomes revealed a 50% overlap independent of the used coating substrates. Inflammatory activation of enteric glia by IL-1β treatment showed distinct coatingdependent gene expression signatures, with an enrichment of genes related to myeloid and epithelial cell differentiation on Matrigel and laminin coatings, while poly-L-ornithine induced more gene sets related to lymphocyte differentiation.Discussion: Together, changes in morphology, differentiation and immune activation of primary enteric glial cells proved a strong effect of the ECM. We identified Matrigel and laminin as preeminent substrates for murine enteric glial cultures. These new insights will help to standardize 2 and improve enteric glial culture quality and reproducibility between in vitro studies in the future, 40 allowing a better comparison of their functional role in enteric neuroinflammation.